Pengaruh Penerapan Model Problem Based Learning Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Akuntansi Perusahaan Dagang - Shella Anggraeni Hasandi; Ria Herdhiana; Sungging Handoko (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2015)
Students' thinking ability can be improved through learning, but the teacher's effort in implementing the learning is not yet oriented to the students to improve the thinking ability of high level especially the critical thinking ability. Based on these problems, it needs an innovation in learning that aims to find a suitable learning model to improve critical thinking skills. The research method used is experimental method Implementation of research conducted at SMK Negeri 3 Bandung with study population is the students of class XI majoring in Accounting. Sampling using purposive sample technique. The results are obtained as follows. (1) The application of PBL model in the experimental class is done very well (2) There is a difference of mean of students' critical thinking ability on the subject of cut, return and lightness in the experimental class applying the PBL model and the control class using the teacher's usual learning. (3) Improvement of students' critical thinking skill on cutting, return and lightness in experiment class is higher, because there is a significant improvement and control class does not increase significantly which can be seen from the gain test result with high interpretation result in experimental class and moderate in the control class. This happens because the syntax of the PBL model supports the students to improve their critical thinking skills.